Underage Drinking in America: An Explanation through the Lens of the General Theory of Crime. Issue 1 (2nd January 2020) - Baek, Hyunin; Lee, Selye
ABSTRACT: Despite the high rate of drinking among adolescents and its negative consequences, studies regarding causality of drinking behaviors have been under-examined. Regarding causal factors of underage drinking, Gottfredson and Hirschi's general theory of crime provided a useful theoretical frame. Using the data set of "Monitoring the Future: A Continuing Study of American Youth, " this study conducted multiple regression analyses with the selected sample data set of 4, 626. The results indicated that adolescents with a lower self-control were more likely to drink than those with a high self-control. Furthermore, opportunity (i.e., accessibility of alcohol and drinking peers) was a strong predictor of underage drinking. Particularly, this study found a significant effect of the interaction between low self-control and opportunity on drinking among American youth. Thus, this study strongly supports the general theory of crime as well as provides an approach to reduce underage drinking in America.